EVALUASI DIMENSI PERABOT PADA RUANG PERPUSTAKAAN UMUM LAMONGAN BERDASARKAN ANTROPOMETRI DAN ERGONOMI - agustapraja, hammam rofiqi; Windarto, Singgih Jiar (Aksen : Journal of Design and Creative Industry, 2021)
The Lamongan public library is one of the public facilities for the Lamongan community which functions as a medium for distributing information and knowledge to all levels of society. Of these facilities, the most influential are physical facilities such as tables, chairs, bookshelves. Dimensions or physical facilities in a library also affect the comfort of its users. Therefore, this study aims to determine whether the dimensions of the furniture in the Lamongan public library are by the standard with anthropometric and ergonomic comparisons of visitors. This study uses a quantitative descriptive method, namely by collecting data on the visitor’s body size, and later it will be compared with the furniture variables used. The results of research and calculations show that the furniture in the Lamongan public library room, such as chairs, 100% is said to be feasible, 33.5% type A table is included in the category of not meeting and 66.5% has met, 33.5% type B table is included. The category does not meet and 66.5% has met, for the bookshelf in the library room it can be said to be feasible because it is by anthropometric calculations, suggestions from the results of this study are to maintain what is feasible and adjust furniture that is not appropriate to the size of the visitor’s body.